Cross-border reproductive care: Psychological distress in a sample of women undergoing in vitro fertilization treatment with and without oocyte donation - Lasheras, Gracia; Mestre-Bach, Gemma; Clua, Elisabet; Rodríguez, Ignacio; Farré Sender, Borja (International Journal of Fertility and Sterility, 2020)
Background: Cross-border reproductive care (CBRC) refers to the movement of patients to foreign countries for fertility treatment. Limited evidence indicates that this phenomenon is associated with a risk of psychological distress, but few studies on the psychological impact of CBRC are currently available. The aim of this study was to compare the anxiety and depression levels of a group of cross-border patients with a local Spanish patient group, both of which underwent in vitro fertilization (IVF) treatment. We also sought to explore the clinical, sociodemographic and personality profiles of the CBRC group and local women. Materials and Methods: This present cross-sectional study was conducted on 161 infertile females (71 CBRC patients and 90 local women) who were undergoing IVF treatment. The following questionnaires were used to collect data: Spielberger State Anxiety Inventory (STAI-S), the Beck Depression Inventory-II (BDI-II) and the Zuckerman-Kuhlman Personality Questionnaire (ZKPQ). Sociodemographic, clinical, reproductive and CBRC variables were also recorded. Results: CBRC patients, specifically CBRC oocyte recipients, showed higher levels of anxiety compared to local women. However, no significant differences in depression scores were found between both groups. Finally, when analysing personality, the Activity scale scores of the ZKPQ were found to be higher in CBRC oocyte recipients, which indicated a greater tendency for general activity and higher energy levels. Conclusion: CBRC oocyte recipient women may have greater vulnerability to anxiety than local women prior to infertility treatment. Screening and psychological support protocols for anxiety in this population should be considered.
Keywords: assisted reproductive technologies; in vitro fertilization; oocyte donation; personality; psychopathology; Scopus; JCR